The mechanism to contribute during the establishment of a commercial company - Ханієва, Фатіма Магомедівна (Problems of legality, 2016)
The author analyzed the mechanism for making capital contributions to the authorized (share) capital during the process of establishment a commercial company. Attention was paid to different scientific views and concepts for determination of the legal essence of company’s founders’ /members’ action system when they make their contributions. The scientific research of «ideal form» for such mechanism, both before and after the registration of a company, found that it is the acts of founders/members that are not devoid of specificity and are qualify as specific corporate (due to the irreversibility of the state registration of a company) or treaty, or those that are generated by one-sided deal. If the company was established by one founder, then the process of making capital contributions is a unilateral contract as a decision of only founder. Besides, the researcher conducted a comparative legal analysis of current Ukrainian legislation and law of foreign countries such as France, the Czech Republic and Latvia. As the results, it was found that the acts of founders/members to contribute to the authorized (share) capital are specific with defined difference.